Study of Productivity of Smallholder Oil Palm Plantations Based on Region in North Sumatera Province Indonesian - Jones Simatupang; Manaor Bismar Posman Nababan; Aditia Erick Cantona Simatupang (ITScience (Information Technology and Science), 2026)
This study aims to determine the differences in productivity and factors influencing the productivity of smallholder oil palm plantations in North Sumatera based on regionalization. Sampling was conducted using a multi-stage approach in three districts known to have the largest area of smallholder oil palm plantations in North Sumatera, representing the West Coast Highlands and West Coast regions. Each district is represented by one sub-district and two villages. The total sample was 450 farmers from 75 samples representing each selected village. The analysis conducted involved the One Way ANOVA Test and the Tobit Regression Test. The results of the study indicate significant differences in the productivity of smallholder oil palm plantations in North Sumatera Province based on zoning, with productivity levels categorized as follows: West Coast > East Coast > Highlands. Simultaneously, all socio-economic factors have a significant effect on the productivity of smallholder oil palm plantations. Factors that significantly affect the productivity of smallholder oil palm plantations are labor, fertilizer, gender, and type of seed applied in all three regions. Factors of land area, farming experience, and access to credit apply in two regions (Highlands and West Coast). Farmer education factors apply only in one region (Highlands). Factors that do not affect the three regions are pesticides.